2022
DOI: 10.1017/s0956536120000413
|View full text |Cite
|
Sign up to set email alerts
|

Defining Rurality at La Joyanca (Peten, Guatemala): Architecture, Land Use, and Social Dynamics

Abstract: Considering the Classic Maya lowlands as an intricate landscape of nested settlements with cities, villages, and farmsteads in the middle of agricultural land, the rural/urban conceptual contrast would apparently apply, yet, is still debated. By combining detailed studies of the relationships between populations of both categories, one can better understand what rurality and urbanity meant in ancient Maya societies, and evaluate the dichotomy. Judging by the spatial distribution of architecture and the social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…My emphasis here on rural research is not a call to abandon scholarship on ancient Maya cities. Urbanism studies are as critical as rural research since the two mutually inform each other and, as shown by some of the following contributions, urban and rural life are interconnected and can be interdependent (Lemonnier and Arnauld 2022; also see Garrison et al 2019; Hutson 2016; LeCount and Yaeger 2010; Yaeger 2003). For this reason, some scholars (e.g., Lemonnier and Arnauld 2022; Marcus 1983; Yaeger 2003) have argued that they should, in fact, be studied together.…”
Section: Rural Stereotypes and Urban-centrismmentioning
confidence: 99%
See 4 more Smart Citations
“…My emphasis here on rural research is not a call to abandon scholarship on ancient Maya cities. Urbanism studies are as critical as rural research since the two mutually inform each other and, as shown by some of the following contributions, urban and rural life are interconnected and can be interdependent (Lemonnier and Arnauld 2022; also see Garrison et al 2019; Hutson 2016; LeCount and Yaeger 2010; Yaeger 2003). For this reason, some scholars (e.g., Lemonnier and Arnauld 2022; Marcus 1983; Yaeger 2003) have argued that they should, in fact, be studied together.…”
Section: Rural Stereotypes and Urban-centrismmentioning
confidence: 99%
“…Urbanism studies are as critical as rural research since the two mutually inform each other and, as shown by some of the following contributions, urban and rural life are interconnected and can be interdependent (Lemonnier and Arnauld 2022; also see Garrison et al 2019; Hutson 2016; LeCount and Yaeger 2010; Yaeger 2003). For this reason, some scholars (e.g., Lemonnier and Arnauld 2022; Marcus 1983; Yaeger 2003) have argued that they should, in fact, be studied together. To do so, however, requires increasing the number and intensity of rural-focused investigations to comparably reach the abundance of information gained on major and secondary ancient Maya centers.…”
Section: Rural Stereotypes and Urban-centrismmentioning
confidence: 99%
See 3 more Smart Citations